Improved Energy Efficient Wireless Sensor Networks Using Balanced Multi-Hop Routing Protocol - Sivakumar, C; Latha Parthiban, P (International Journal of Engineering and Technology, 2018)
In this paper, consumption of energy by the sensor nodes in Wireless Sensor Nodes (WSNs) is been handled effectively using a combined technique. The objective of the paper is to increase the network lifetime with dynamic routing protocol. Here, the proposed routing algorithm, named Balanced Multi-Hop (BMH) protocol combines the multi-hop and direct transmission communication. This method further uses Dijkstra algorithm to route the packets between the sensor nodes and base station in mobile network. This method avoids the use of central router to control the other nodes. The results of the proposed method is tested against various result metrics. The evaluation over other existing methods prove that the BMH method achieves higher lifetime and high network throughput.Â Â